Internet of Things assisted radio frequency identification based mine safety management platform. (14th September 2020) - Xie, Xionghui; Lin, Rongping; Yu, Bo; Wen, Wenfu; Gu, Fahui; Sivaparthipan, C.B.; Vadivel, Thanjai
Abstract: The production of any mine depends heavily on the secure relation between human and mining equipment. Protecting and optimizing the use of these tools and workers from potential accidents by real‐time monitoring and control will greatly improve mine safety and productivity. As an emerging technology, the Internet of Things (IoT) and radio frequency identification (RFID) provides a new strategy for underground production of mine security and safety. The main technologies of the Internet of Things are introduced in line with the required of mine safety production. The innovation used in this process is RFID technology, sensor technology for the conceiving of things, intelligent technology for thinking about things, and inherent security technology. In this article, the adaptive heuristic mathematical model based on IoT and RFID real‐time monitoring systems has been proposed for the production of mine safety and analysis. This system allows for real‐time tracking, detecting suspicious incidents, and verification of the position of a miner within the harsh underground mining environment. The major involvement of this research is the cost‐efficient framework to efficiently promote the protection of underground coalmines. This system helps solve serviceability, accessibility, flexibility, and interoperability problems in coal mines.